고압 인젝터의 동적 거동을 고려한 최적 틈새 조합에 관한 연구 - 류대원(Daewon Ryu); 김동준(Dongjun Kim); 박상신(Sang-Shin Park); 류봉우(Bongwoo Ryu) (Tribology and Lubricants, 2021)
An injector is a mechanical device present inside the engine. Its main function is to supply an appropriate volume of fuel into the combustion chamber, which is directly related to the overall engine efficiency of a car. During the operation of an injector, a magnetic force lifts the parts of the injector from closed position to open position which generates a horizontal force on the needle. The horizontal force acts on a different position from that of the center of mass of the needle. Therefore, this causes eccentricity in the needle and the generation of a tilting motion during the lifting operation which can result in wear. However, appropriate selection of clearances for these parts can prevent wear. In this study, lubrication analysis is conducted to determine the optimum clearance of parts with sliding motion inside the injector. The height functions are derived considering the dynamic behavior and relative velocity of the parts. Using the derived height function, the pressure profiles are calculated for the lubricated surfaces from the Reynolds' equation. Subsequently, the fluid reaction forces are calculated. The equations of motions are applied to the fluid reaction forces and external forces are solved to calculate the minimum film thickness between each part with variation in the clearances. Finally, the optimum clearances are determined. The effect of the clearances on the behavior of the moving parts is presented and discussed.